Kaneki Ken’s Character Arc: A Hero’s Journey Analysis - Hafiz Priansyah (Universitas Pendidikan Indonesia (UPI), 2018)
Literature has a trend that has grown its fame across the globe, called manga. They are similar in form with Western comic books, but with a different style and structure of the story’s presentation. One of the key elements of a manga’s story, the characters, pique the interest of the researcher. Kaneki Ken is the protagonist of the Tokyo Ghoul series that possesses this interesting characterization to look into. He goes through a journey that changes his characterization in a certain point in the story. To analyze this characterization, two analysis methods are used; Vogler’s (1996) hero’s journey theory and Sicoe’s (2013) character arc theory. The hero’ journey theory is used to gain an understanding of the events Kaneki goes through in his story, while the character arc theory is used to determine the kind of change he experiences. The result shows that Kaneki’s journey is a tragic hero’s journey, different from the traditional hero’s journey, and that he experiences the fall arc, which is, essentially, a tragedy. Furthermore, analysis of Kaneki’s unorthodox hero’s journey leads to the discovery of how an idolized character can start a serialization of literature, and how a serial literature, especially mangas, tend to be devious towards the hero’s journey theory. Keywords: Transitivity, Critical Discourse Analysis, Language and Gender, Literary Texts, Representation